Gonadotropin ratio affects the in vitro growth of rhesus ovarian preantral follicles. Issue 4 (April 2016) - Kim, Yoon Young; Yun, Jun-Won; Kim, Jong Min; Park, Chung Gyu; Rosenwaks, Zev; Liu, Hung Ching; Kang, Byeong-Cheol; Ku, Seung-Yup
Abstract : In vitro follicle growth (IVFG) strategy is critical in the fertility preservation of cancer survivors; however, its optimal protocol needs to be developed using primate models since the availability of human samples is limited. Only a few previous studies have reported the successful IVFG of rhesus monkey ovaries using low-dose follicle-stimulating hormone (FSH) (0.3 or 3 ng/mL) and long-term culture (up to 5 weeks) and it is still uncertain in regard to the optimal culture duration and effective dose of treated gonadotropins applicable to the IVFG of rhesus preantral follicles. Recently, we have reported that the FSH to luteinizing hormone (LH) ratio affects the in vitro growth of murine ovarian follicles. We aimed to investigate whether gonadotropin ratios affect the efficiency of rhesus follicular growth in vitro . Ovaries were collected from six necropsied rhesus macaques (4–9 years) and preantral follicles were retrieved and cultured for 14 days using 200 mIU/mL FSH. The characteristics of follicular growth were compared between the FSH:LH=1:1 (n=24) and FSH:LH=2:1 (n=24) groups. High concentration gonadotropin treatment shortened the duration required for in vitro maturation of rhesus preantral follicles. The FSH:LH=2:1 group showed a faster follicular growth and enabled the acquisition of mature oocytes, although the expression of growth differentiation factor (GDF)-9 and anti-Müllerian hormone (AMH) did not differ significantly between the two groups. Taken together, high dose gonadotropin treatment can shorten the duration of IVFG and the gonadotropin ratio is important in the IVFG of rhesus monkey ovaries.